PENGEMBANGAN MODEL PEMILIHAN LOKASI PEMBUANGAN AKHIR SAMPAH PERKOTAAN (STUDI KASUS: KOTA JAKARTA TIMUR) - Usman, Yulita Veranda; Ismail, Asrul Harun; Hidayah, Nur Yulianti; Chairani, Laela (Jurnal Ilmiah Teknik Industri, 2013)
Determination of temporary shelters garbage (TPS) and the final disposal site (TPA) is a very important, that pile of garbage does not interfere the daily activity of society, their comforts, and the beauty of the city. City government has set the TPS at all kelurahan, such as in Kota Jakarta Timur.  There are a number of polls spread over 60 kelurahan and 10 districts. Meanwhile, the TPA is available only 3 locations spread and allocated to accommodate waste from around the TPS in Jakarta. Therefore in this study developed a model of urban waste disposal site selection based on their shortest distance using binary integer linear programa method with the help of microsoft excel solver. As for the data used in them is the location of the TPS and TPA, as well as the distance between them, which is derived from Dinas Kebersihan Jakarta Timur, Central Board of Statistics (BPS), and google maps. Optimization model is expected to help the government in determining the exact location of each TPA TPS.